Simultaneous removal of organic and inorganic pollutants from landfill leachate using sea mango derived activated carbon via microwave induced activation - Shehzad, A. (Walter de Gruyter GmbH, 2016)
The present work reveals the preparation and optimization of sea mango based activated carbon (SMAC) by microwave induced KOH activation for the adsorptive removal of organic and inorganic contaminants from the mature anaerobic landfill leachate using response surface methodology (RSM) technique. Chemical oxygen demand (COD) and ammoniacal nitrogen (NH3-N) are the main indicators for organic and inorganic compounds often found in aged landfill leachate. Hence, the treatment of this stabilized landfill leachate is considered to be an essential step prior to its discharge. The leachate sample was collected from Sahom Landfill site in Perak, Malaysia and the initial concentrations of COD and NH3-N were measured as 550 mg/L and 3,330 mg/L, respectively. The feasibility of converting Sea mango to activated carbon process to remove the COD and NH3-N pollutants from landfill leachate was investigated. The preparation conditions such as microwave heating at power range (350-600 W), impregnation of AC with KOH (0.5-3.0) and retention time (6-10 min) were evaluated, analyzed and optimized using response surface methodology (RSM). From the analysis of variance (ANOVA), the optimum conditions for preparation of SMAC was at 560 W of activation power, 8.4 min of activation time and 2.10 of impregnation ratios with higher adsorptive removal of COD (72.50 ), and NH3-N (79.77 ), respectively. The physical and chemical properties of SMAC were evaluated by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and surface area. The findings exemplified the applicability of SMAC as an effective precursor for the simultaneous removal of organic and inorganic pollutants from mature landfill leachate. Â© 2016 by De Gruyter.